PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIIIE SMP NEGERI 4TUALANG - Khotimah, Rizky; Syofni, Syofni; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACTThis study was conducted at SMP Negri 4 Tualang in the second semester of the school years 2012/2013. The subject of the research is students of class VIIIE. There are 36 student in that class, consisting 18 girl and 18 boys who have heterogeneous academic ability. The goal of this study is to improve students’ mathematics achievement, especially in geometrical (cubes, blocks, prisms, and limas) by applying the Cooperative Learning Think Pair Square Approach. This study is an action research. There are two cycles and four stages in this study. Each cycle has four stages, they are planning, action, observation, and reflection. The result of research showed that the improvement of students learning achievement. The percentage of first cycle showed that students who get minimum achievement criteria (MMC), from 50% to 72,22%. While, in the second cycle, the percentage of students who minimum achievement criteria (MMC) increase to 91,66%. In other words, the implementation of Cooperative Learning Think Pair Square can improve students’ mathematics achievement in class VIIIE of SMP Negeri 4 Tualang, especially in geometrical in the school years 2012/2013.          Key words: Cooperative Learning, Think Pair Square, Learning Achievement